Reviu Statistika: Data Dan Skala Pengukuran - Mula Tarigan; Dewi Frintiana Silaban (JINTAN: Jurnal Ilmu Keperawatan, 2023)
Statistics is a set of concepts, rules, and methods used in each step of the nursing research process. In order to produce valid and reliable research outputs, it is imperative that researchers understand the fundamentals of statistics, especially novice researchers and nursing students. This paper aims to explain briefly the most fundamental part of statistics. Still, it plays an important role in the early stages of the research process and preparation for the process of data analysis. To make this writing easier to understand, the contents of the material are complemented by various examples in real situations and presented in tables and figures. This paper is the first of a series of articles on statistics in nursing research.